Prevalence of Supernumerary Teeth in Patients with Cleft lip and Palate through Orthopantomographic Analysis: A Systematic Review - Abbas Salehi Vaziri; Atefe Ahmadvand; Anahita Dehghani Soltani; Seyed Masoud Sajedi; Shahoon, Hossein (Galen Medical Journal, 2024)
Background: One of the most common injuries in the jaw and face area is cleft lip and palate, which causes an increase in the size, shape and time of formation and growth of teeth. Early detection of the number of missing teeth and paying attention to the size, shape and number of the remaining teeth is one of the goals of this study. Materials and Methods: The present study investigated the issue by reviewing 45 articles with keywords including “Supernumerary teeth”, “Cleft lip”, “Palate”, “Orthopantomo graphic” and “Hospital Infection” in 2012 to 2024. Results: The most common abnormality was hypoxemia, followed by malocclusion and hyperemia. The most cases of hypoxemia were observed in bilateral cleft lip and palate, and the lowest cases were found in single cleft lip. Many problems that arise in the mouth and teeth can be solved by observing health and care tips and also by teaching children how to brush their teeth correctly, but one of the things that is necessary and necessary for children’s health is regular and periodic dental visits. In these visits, many oral and dental problems are revealed and they can be solved before more problems occur and high dental costs can be avoided. One of the problems of extra teeth in children is that if it is identified in the early stages, it can be treated and damage to other teeth can be prevented. Conclusion: Extra teeth may cause delayed growth or non-growth of adjacent teeth. In addition, excessive retention of baby teeth, deformation of the roots of adjacent permanent teeth, displacement of teeth, creation of an unnatural distance between teeth, root erosion of adjacent teeth, or the formation of cysts around extra teeth can be among the complications that occur in the presence of teeth. They encountered extra.